Analisis Metode Analytic Hierarchy Process Dalam Sistem Pendukung Keputusan Pemilihan Taruna Berprestasi - Lisda Juliana Pangaribuan; Tiara Sylvia; Liber Tommy Hutabarat (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Process of selecting outstanding cadets is a multi-criteria problem, so get objectively achieving cadets, a decision support system with multiple criteria is needed. As an appreciation for achievement, a few universities provide scholarships for high achieving students. However, a few universities choose outstanding students based only on GPA. This study aims to analyze the application of the Analytic Hierarchy Process (AHP) method in the Decision Support System for the selection of cadets so that objectively achieving candidates can be determined. Because the number of prospective cadets with many achievements, Random Index (IR) value is obtained from IR table > 15. This study uses 4 criteria, namely the GPA criteria with eigenvectors = 0.111, Scientific works with eigenvectors = 0.563, extracurricular (Achievement) with eigen vector = 0.246 Foreign language proficiency with eigenvector = 0.08. From the research results obtained the value of CR = -0,987 <= 0.1, then the value of the comparison criteria is consistent. The results showed that there were differences in the ranking of outstanding cadets at the Medan Aviation Polytechnic according to the GPA and the AHP method